Evapotranspiration and land surface temperature of typical urban green spaces in a semi-humid region: Implications for green management - Li, Xinhao; Li, Yiran; Di, Suchuang; Niu, Yong; Zhang, Chuanjie (Frontiers in Environmental Science, 2022)
Ecological deterioration and water scarcity motivate people to seek a balance between ecological reserves and water consumption in cities located in Semi-humid regions. This study is designed to develop a method for evaluating cooling water-saving characteristics of green space structures. Land surface temperature (TS), vegetation quantity (VQ) and evapotranspiration (ET) of typical green vegetation structures in 50 plots with an average area of 10000 m2 were studied. Parameters were obtained based on data from three temporal remote sensing images; the surface energy balance algorithm for land (SEBAL) model, single-channel algorithm, and normalized difference vegetation index (NDVI) were utilized in the calculation. The relationships between the TS, VQ, and ET of green land were explored using regression analysis. A comprehensive index (EWI) was proposed to evaluate the cooling and water-saving abilities of different green space structures. Based on assessment results, species were classified into three: good (EWI ≥ 0.795), common (0.795 ＞ EWI ≥ 0.419), and weak (EWI ＜ 0.419). The characteristics of 17 species or species compositions with good cooling and water-saving abilities were summarized as: (a) a mix of the arbor, shrub, and herb, and (b) complete cover of green space by shrub.